An approach to the problem of employment in India - Deepankar Basu (University of Massachusetts, Department of Economics, 2018)
The challenge of employment in the Indian economy, especially after it growth acceleration since the mid-1980s, relates to its quality rather than its quantity. While employment growth has kept pace with the labour force over the long run, what has grown is informal employment. The coexistence of rapid capital accumulation, robust output growth and lack of growth of formal employment can be understood using the well-known Harris-Todaro model of a dual economy. This framework highlights the key role of the wage gap between the modern and traditional sectors as a determinant of urban informal employment. Hence, one of the most effective and egalitarian ways to address the employment problem is to adopt policies to increase agricultural productivity and income, which can reduce the wage gap. Since crop yields in India are far lower than many other countries in the world, including China, Brazil, and Bangladesh, there is ample scope for land-augmenting and labour-absorbing technological change in Indian agriculture. Efforts to ramp up industrialization should be taken up in earnest only after the wage gap has been narrowed significantly.
Keywords: J21; O10; O13; 330; employment; India; Harris-Todaro; agriculture